2015
DOI: 10.3389/fncel.2015.00076
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte heterogeneity in the brain: from development to disease

Abstract: In the last decades, astrocytes have risen from passive supporters of neuronal activity to central players in brain function and cognition. Likewise, the heterogeneity of astrocytes starts to become recognized in contrast to the homogeneous population previously predicted. In this review, we focused on astrocyte heterogeneity in terms of their morphological, protein expression and functional aspects, and debate in a historical perspective the diversity encountered in glial progenitors and how they may reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 98 publications
(166 reference statements)
0
93
0
Order By: Relevance
“…Activation of these receptors triggers dynamic changes of concentration of ions (mainly Ca 2+ and Na + ) in the astroglial cytoplasm, which regulate astroglial functions and serve as a substrate for astroglial excitability (Agulhon et al ., 2008; Kirischuk et al ., 2012; Parpura and Verkhratsky, 2012b, 2013; Rose and Karus, 2013; Verkhratsky et al ., 2014c; Zorec et al ., 2012). The functions of astrocytes are highly diverse and are regionally specialized (Anderson et al ., 2014; Chaboub and Deneen, 2012; Matyash and Kettenmann, 2010; Oberheim et al ., 2012; Parpura et al ., 2012; Schitine et al ., 2015). In the gray matter astrocytes divide (through the process known as tiling that starts in the late embryogenesis) the parenchyma into relatively independent units, traditionally known as neurovascular units and recently often called astroglio-vascular units, that integrate, within an individual astroglial territorial domain, neural and vascular elements (Bushong et al ., 2002; Iadecola and Nedergaard, 2007; Nedergaard et al ., 2003).…”
Section: Astrogliopathology: Reactivity Atrophy With Loss Of Funcmentioning
confidence: 99%
“…Activation of these receptors triggers dynamic changes of concentration of ions (mainly Ca 2+ and Na + ) in the astroglial cytoplasm, which regulate astroglial functions and serve as a substrate for astroglial excitability (Agulhon et al ., 2008; Kirischuk et al ., 2012; Parpura and Verkhratsky, 2012b, 2013; Rose and Karus, 2013; Verkhratsky et al ., 2014c; Zorec et al ., 2012). The functions of astrocytes are highly diverse and are regionally specialized (Anderson et al ., 2014; Chaboub and Deneen, 2012; Matyash and Kettenmann, 2010; Oberheim et al ., 2012; Parpura et al ., 2012; Schitine et al ., 2015). In the gray matter astrocytes divide (through the process known as tiling that starts in the late embryogenesis) the parenchyma into relatively independent units, traditionally known as neurovascular units and recently often called astroglio-vascular units, that integrate, within an individual astroglial territorial domain, neural and vascular elements (Bushong et al ., 2002; Iadecola and Nedergaard, 2007; Nedergaard et al ., 2003).…”
Section: Astrogliopathology: Reactivity Atrophy With Loss Of Funcmentioning
confidence: 99%
“…Others have demonstrated regional differences among astrocytes in the expression of cytoskeletal elements and neuropeptides, and in the uptake of neurotransmitters (Wilkin et al, 1990). Regional differences in astrocytes have been observed in a variety of disease states, including Alzheimer’s Disease, amyotrophic lateral sclerosis, and major depression (Schitine et al, 2015). However, in many of these situations, it has been unclear whether the regional differences in astrocytes are due to intrinsic differences in the astrocytes themselves or to regional differences in neuronal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Regional differences in astrocyte physiology exist across the brain (Bonthius and Steward, 1993; Schitine et al, 2015). Thus, astrocytes in some regions may be differently affected by certain GFAP mutations than astrocytes in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the dysfunction of these may lead to the development of various neuropathological diseases, such as major depression. 13) Actually, it has been demonstrated that both proliferations of neurons and astrocytes are inhibited in the cortex. 14) Moreover, histopathological studies have demonstrated a decrease in the density of astrocytes in postmortem brain tissue in major depression.…”
Section: )mentioning
confidence: 99%